2020
DOI: 10.1515/opag-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiosensitivity study on wheat (Triticum turgidum ssp. durum)

Abstract: Fifty wheat seed variety (var.) CIRNO C2008 were gamma irradiated with 100, 200, 300, 400, 500, or 600 Gy by using a Cobalt-60 source at 907.39 Gy/h, and the nonirradiated seeds were considered the control (M0). A photoperiod of 13 h of darkness (14°C) and 11 h of light (2 h at 18°C, 7 h at 25°C, and 2 h at 18°C) was used for 30 days, in a growth chamber (BJPX-A450; BIOBASE) for quantifying the morphometric traits of the irradiated vs nonirradiated seeds. The germination percentage (from 88.89% in M0 to 77.78%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…We can also agree with previous studies of this mutagen in other cereal crops, primarily in terms of depressive effects in the first generation and induction of mutations, that, in general, the concentrations proposed for practical use are sufficiently contrasting to obtain a wide variety in the largest possible group of genotypes (Zhao et al, 2019;Ahumada-Flores et al, 2020). Other effects are possible, but primarily in groups that are of more limited interest -with the presence of significant translocations from wild relatives, perhaps some specific local forms and landraces (Pekol et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We can also agree with previous studies of this mutagen in other cereal crops, primarily in terms of depressive effects in the first generation and induction of mutations, that, in general, the concentrations proposed for practical use are sufficiently contrasting to obtain a wide variety in the largest possible group of genotypes (Zhao et al, 2019;Ahumada-Flores et al, 2020). Other effects are possible, but primarily in groups that are of more limited interest -with the presence of significant translocations from wild relatives, perhaps some specific local forms and landraces (Pekol et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…However, as can be seen from the response of some variants, this may narrow the possibilities for the emergence of promising forms in the future for some less variable initial subjects (Nazarenko, 2020). Thus, the position on expansion of the used gradations of the mutagenic factor remains unchanged, since even in this study there are at least two of these forms out of eight, in fact, a quarter of the sample, which is very significant (Ahumada-Flores et al, 2020;Von Well et al, 2022).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We mention that the radiosensitivity of wheat studied by Ahumada-Flores et al [ 39 ] indicated that gamma ray irradiation at doses lower than 100 Gy causes positive morphological changes in its growth, while higher doses (300, 400, 500 and 600 Gy) negatively affect plant growth and survival due to deleterious effects that reduce plant genome stability, such as chromosomal damages. Im et al [ 35 ] found that low-dose proton beam irradiation did not affect the height of soybean plants compared to high doses of 100–300 Gy.…”
Section: Discussionmentioning
confidence: 99%